HUBUNGAN PEMBELAJARAN SELF-REGULATED DENGAN HASIL BELAJAR SISWA MI DI OKU TIMUR - Siti Nurjanah; Nasikhotun Nadiroh; Naila Rohmaniyah; Elina cahyanti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article reports students’ low learning outcomes of MI Subulussalam 02 Sriwangi and students’ lack of awareness to be active in the learning activity in order to achieve learning outcomes. Hence, there are still many students who have difficulty managing their time in learning. The research is intended to find out the relationship between self-regulated learning and students’ learning outcomes. Self-regulated learning is the independent variable (influencing variable) and students’ learning outcomes are the dependent variable (influenced variable). The method used is the quantitative research method. The analysis result is that there is a correlation between self-regulated learning and students’ learning outcomes with a significant value of 0.003 < 0.05. The minimum value is 115 and the maximum value is 140 on the self-regulated learning variable, while students’ learning outcomes indicate a minimum value of 58 and a maximum value of 84. The value of rcount is 594, which indicates a relationship between self-regulated learning and students’ learning outcomes at the moderate or sufficient level. The rcount value of -.594 indicates a negative number,which means that there is a correlation between the two variables that are opposite.